Analisis Perencanaan Tebal Perkerasan Kaku Lajur Pengganti pada Proyek Pembangunan Jalan Tol Jakarta-Cikampek II Elevated - Rahmat Ardiansyah; Tri Sudibyo (Jurnal Teknik Sipil dan Lingkungan, 2020)
Road widening is a construction phase of Jakarta-Cikampek II elevated Toll Road construction project. Improving the effectiveness and road service capability influence the traffic activity. This study aimed to analyze alternative rigid pavement design and thickness based on the Road Pavement Design Manual (MDPJ) 2017 and American Association of State High-way and Transportation Officials Guide for Design of Pavement Structures (AASTHO) 1993. This research was conducted on March – May 2019. Based on the obtained data, a rigid pavement design alternative using the MDPJ 2017 method showed concrete plate thickness of 305 mm and using the AASHTO 1993 concrete plate thickness was 320 mm. In actual condition the concrete plate thickness was 300 mm.